South Asia Economic Focus, Spring 2019 : Exports Wanted - World Bank (Washington, DC: World Bank, 2019)
South Asia remained the fastest growing region in the world last year, but growth remained driven by domestic demand – and not exports – which resulted in another year of double-digit volume growth of imports. The value of imports was further pushed up by rising oil prices. The widening current account deficits became more difficult to finance and these tensions triggered capital outflows, depreciation pressures, increases in credit default swap spreads, and falling stock prices. In recent months, however, the data shows a more positive picture. The growth outlook for South Asia assumes that the recent acceleration of export growth continues and that import growth slows. Under these conditions, GDP growth is expected to accelerate. Under current circumstances fiscal tightening is appropriate, not only to make government debt more sustainable, but also to bring the economy back into balance, and thus become less vulnerable to deteriorating conditions in international financial markets. Using a gravity model, we show that South Asian countries export only a third of their potential. If countries export closer to potential, not only would short-term adjustments be easier, but also the long-term growth potential would be higher. Closing the export gap is an essential step in addressing both short-term and long-term macroeconomic challenges in South Asia.